Differential Impact of Age and Cytomegalovirus Infection on the γδ T Cell Compartment - Roux, Antoine; Mourin, Gisèle; Larsen, Martin; Fastenackels, Solène; Urrutia, Alejandra; Gorochov, Guy; Autran, Brigitte; Donner, Catherine; Sidi, Daniel; Sibony-Prat, Joyce; Marchant, Arnaud; Stern, Marc; et al. (The Journal of immunology (1950), 2013)
γδ T cells represent a subset of unconventional T lymphocytes that are known for their reactivity against different pathogens and considered as intermediate mediators between adaptive and innate immunity. We provide in this paper further insights underlying the changes that affect the γδ T cell compartment with advanced age in humans. We show that both aging and CMV infection impact independently on the γδ T cell compartment. Most γδ T cells are significantly affected by age and present a decreased frequency in the elderly. The decline of the γδ T cell pool appears to be independent from the activity of the thymus, arguing in favor of an extrathymic site of γδ T cell production in humans. Of note, CMV infection, which is directly associated with the activation of the pool of Vδ2− γδ T cells, promotes nonetheless the inflation of this compartment throughout life. CMV seropositivity accentuates further the accumulation of highly differentiated lymphocytes in Vδ2− γδ T cell subsets with time, in contrast to Vδ2+ γδ T cells, which maintain a less differentiated phenotype. This is similar to the effect of CMV on αβ T cells and suggests that γδ T cells may vary in differentiation phenotype according to distinct stimuli or pathogens.